Product Marketing Strategy Effective: Key Maximizing Business Profits - Ian Zulfikar (SEAN Institute, 2025)
In a competitive business environment, selecting and implementing the right marketing strategy is key to attracting consumers, increasing sales, and building customer loyalty. This study examines the importance of an effective product marketing strategy as a key factor in maximizing business profits. The study used a qualitative approach with descriptive methods. The results show that a well-planned marketing strategy, from understanding the target audience and determining pricing to selecting promotional channels, positively impacts sales growth and customer loyalty. The use of social media, engaging promotions, and word-of-mouth marketing have proven effective in expanding market reach and building consumer trust. Furthermore, strong customer relationships through full-service sales and loyalty programs contribute to repeat purchases, enabling an integrated marketing strategy to sustainably improve business performance.